Training prescription guided by heart-rate variability in cycling - Javaloyes, A.; Sarabia, J. M.; Lamberts, R. P.; Moya-Ramon, M. (International Journal of Sports Physiology and Performance, 2019)
Purpose: Road cycling is a sport with extreme physiological demands. Therefore, there is a need to find new strategies to improve performance. Heart-rate variability (HRV) has been suggested as an effective alternative for prescribing training load against predefined training programs. The purpose of this study was to examine the effect of training prescription based on HRV in road cycling performance. Methods: Seventeen well-trained cyclists participated in this study. After an initial evaluation week, cyclists performed 4 baseline weeks of standardized training to establish their resting HRV. Then, cyclists were divided into 2 groups, an HRV-guided group and a traditional periodization group, and they carried out 8 training weeks. Cyclists performed 2 evaluation weeks, after and before a training week. During the evaluation weeks, cyclists performed a graded exercise test to assess maximal oxygen uptake, peak power output, and ventilatory thresholds with their corresponding power output (VT1, VT2, WVT1, and WVT2, respectively) and a 40-min simulated time trial. Results: The HRV-guided group improved peak power output (5.1% [4.5%]; P = .024), WVT2 (13.9% [8.8%]; P = .004), and 40-min all-out time trial (7.3% [4.5%]; P = .005). Maximal oxygen uptake and WVT1 remained similar. The traditional periodization group did not improve significantly after the training week. There were no differences between groups. However, magnitude-based inference analysis showed likely beneficial and possibly beneficial effects for the HRV-guided group instead of the traditional periodization group in 40-min all-out time trial and peak power output, respectively. Conclusion: Daily training prescription based on HRV could result in a better performance enhancement than a traditional periodization in well-trained cyclists.